2017
DOI: 10.1080/17453674.2017.1338066
|View full text |Cite
|
Sign up to set email alerts
|

Classification systems for distal radius fractures

Abstract: Background and purpose — The reliability of conventional radiography when classifying distal radius fractures (DRF) is fair to moderate. We investigated whether reliability increases when additional computed tomography scans (CT) are used.Patients and methods — In this prospective study, we performed pre- and postreduction posterior–anterior and lateral radiographs of 51 patients presenting with a displaced DRF. The case was included when there was a (questionable) indication for surgical treatment and an addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 25 publications
1
27
0
2
Order By: Relevance
“…Correct identification of fracture extensions into the DRUJ therefore did only negligibly improve with clinical experience and were missed in 61.7 to 66.6% of the cases. Generally, sigmoid notch involvement was found in 84.3% of all scanned fractures, which is similar or slightly higher than numbers from previous reports [4,10,16,22]. Generally, involvement of the sigmoid notch was best identified in axial CT reconstructions, as has been noted by other authors [23].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Correct identification of fracture extensions into the DRUJ therefore did only negligibly improve with clinical experience and were missed in 61.7 to 66.6% of the cases. Generally, sigmoid notch involvement was found in 84.3% of all scanned fractures, which is similar or slightly higher than numbers from previous reports [4,10,16,22]. Generally, involvement of the sigmoid notch was best identified in axial CT reconstructions, as has been noted by other authors [23].…”
Section: Discussionsupporting
confidence: 84%
“…Amongst the most common classification systems of distal radius fractures, however, only the Frykman classification [8] takes into account the involvement of the distal radio-ulnar joint. Few studies with limited patient numbers have compared distal radius fracture extensions using conventional radiographs and computer tomography (CT) [9][10][11], all of which found an underestimation of distal radio-ulnar joint involvement based on plain radiographs.…”
Section: Introductionmentioning
confidence: 99%
“…2 Utilizing CPT codes as a surrogate for fracture severity also poses as a limitation. Inter-rater reliability in assessing the number of articular parts is limited, 19,20 surgeons may charge for a more complex CPT code even if additional fragments are minor or nondisplaced, and fractures with 3 or more parts, corresponding with CPT 25609, likely represents a wide spectrum of injury ranging from minimally-displaced intra articular fractures to those with severe comminution and displacement. For certain complex fractures, multiple surgical approaches, multiple plates, a greater number of screws, and the addition of a dorsal spanning plate or supplemental pinning may be required to achieve an adequate reduction and fixation – these factors, not captured by CPT coding, may influence the cost of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…If fractures were classified on plain radiographs, intra-articular extensions can be missed and fracture severity underestimated. It has been shown that intraobserver reliability of classification systems is better with additional computed tomography (CT) [8,9]. Therefore, in the present study, three-dimensional (3D) CT scans were used to classify intra-articular fractures more accurately.…”
Section: Introductionmentioning
confidence: 97%